Breast Reconstruction: Focus on Implant-Based Reconstruction. - Jon Mikel Rementeria Vázquez; Dariana Martínez Marabotto; Brenda Leticia Rodríguez Bonachea; Yazmín Pérez González; Rodolfo Enríquez Salinas; Luis Arturo Ramírez Riva Palacio; Yair Emmanuel Camacho Almeida; Abigail Cerero Ahuatzin (International Journal of Medical Science and Clinical Research Studies, 2024)
Autologous tissue-based reconstruction and prosthetic implant-based reconstruction are the two main categories of breast reconstruction. The natural feel, size, and form of the breast can be restored by breast reconstruction with breast implants. Following a nipple- and skin-sparing mastectomy and a modified radical mastectomy, implant-based breast reconstruction is most readily executed. The most popular technique for immediate and delayed postmastectomy breast reconstruction is implant breast reconstruction, which makes use of silicone tissue expanders, which were initially utilized for breast reconstruction by Radovan in 1978 and Austad in 1979. As a sign of femininity, breasts might be lost, which can cause a woman great psychological discomfort and negatively impact her sexual life and self-image. Women are given the choice of breast reconstruction following a breast cancer removal treatment, which can enhance their quality of life. However, implant-based reconstruction ought not to be seen as an adjuvant treatment. Procedures like skin-sparing mastectomy and nipple-areola-sparing mastectomy, which enable conservative surgery with an instant implant breast reconstruction, can only be carried out with an early diagnosis.